Collaborating Against Child Abuse: Exploring the Nordic Barnahus Model: Book Review - Nadjwa Aulia Septiani (Journal of Islamic Studies and Education, 2025)
"Beyond The Binary: Gender and Legal Personhood in Islamic Law" by Saadia Yacoob is a groundbreaking work that challenges the traditional binary understanding of gender in Islamic law and explores the legal personhood of individuals who fall outside this binary. The book argues that Islamic law, when interpreted through a lens of justice and equity, can accommodate diverse gender identities and experiences. Yacoob (2024) meticulously examines the historical and contemporary interpretations of gender in Islamic law, highlighting the limitations of the binary framework and its impact on the lives of individuals who do not conform to traditional gender norms. She then presents a compelling case for a more inclusive and nuanced understanding of gender and legal personhood within Islamic law, drawing on Islamic legal principles, feminist scholarship, and contemporary legal developments. This book explores how Islamic jurisprudence constructs gender identity and legal status beyond a simple male/female binary, showing that Islamic law recognizes a variety of gendered legal subjects. Yacoob challenges the idea that gender is the primary organizing principle in Islamic law, showing that other social identities such as age and slavery also play a critical role in defining legal personhood. Through her analysis, Yacoob offers a more nuanced understanding of the Islamic legal tradition, suggesting that the construction of legal personality is relational and situational, shaped by a complex web of social relations. The book advocates an approach that relegates gender as a category of analysis in the study of Islamic law to fully understand the complex and dynamic web of relationships through which power is exercised in legal discourse. As such, “Beyond the Binary” provides new insights into how Islamic law views and regulates gender identity, challenging readers to rethink their assumptions about gender and law in the Islamic context.